Phytate promoted arsenic uptake and growth in arsenic-hyperaccumulator Pteris vittata by upregulating phosphorus transporters. (October 2018) - Liu, Xue; Feng, Hua–Yuan; Fu, Jing–Wei; Sun, Dan; Cao, Yue; Chen, Yanshan; Xiang, Ping; Liu, Yungen; Ma, Lena Q.
Abstract: While phosphate (P) inhibits arsenic (As) uptake by plants, phytate increases As uptake by As-hyperaccumulator Pteris vittata . Here we tried to understand the underling mechanisms by investigating the roles of phytate in soil As desorption, P transport in P. vittata, short-term As uptake, and plant growth and As accumulation from soils. Sterile soil was used to exclude microbial degradation on phytate. Results showed that inorganic P released 3.3-fold more As than that of phytate from soil. However, P. vittata accumulated 2–2.5 fold more As from soils with phytate than that in control and P treatment. In addition, different from P suppression on As uptake, solution uptake experiment showed that As uptake in phytate treatment was comparable to that of control under 0.1–7.5 μM As after 1–24 h. Moreover, responding to phytate, P. vittata P transporter PvPht1;3 increased by 3-fold while PvPht1;1 decreased by 65%. The data suggested that phytate upregulated PvPht1;3, thereby contributing to As uptake in P. vittata . Our results showed that, though with lower As release from soil compared to P, phytate induced more As uptake and better growth in P. vittata by upregulating P transporters. Graphical abstract: Highlights: Phytate promoted As uptake by P. vittata in sterile soils. Phosphate released more As from soils than phytate. Phytate up-regulated expression of P transporter PvPht1;3 . Phytate improved P assimilation, promoting growth of P. vittata . Abstract : Phytate promoted arsenic uptake and growth in P. vittata by upregulating P-transporter PvPht1;3 .